Pengaruh Corporate Governance Terhadap Inefisiensi Investasi Dengan Free Cash Flow Sebagai Pemoderasi - Djaja Perdana; Hasan Subagyo (Akademi Akuntansi YKPN Yogyakarta, 2021)
The level of corporate investment inefficiency is closely related to the effectiveness of corporate governance practices implemented by the largest shareholders and board of directors. This paper discusses empirical research that investigates the impact of the largest shareholders and board size on investment inefficiency with free cash flow as a moderating variable. This study uses a sample of 152 public companies registered in Indonesia’s capital market for the fiscal year ended on December 31, 2014 to 2018. This study uses a multiple regression method with the Ordinary Least Square (OLS) approach. This study find that the largest shareholders and board size are significantly negative impact on investment inefficiency, but the free cash flow doesn’t moderate the influence of board size on investment inefficiency.